The Impact of Heat on Mental Health: Evidence from Indonesia - Limbong, Hendryik Laurencius; Soetjipto, Widyono (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, 2025)
This study examines the impact of air temperature on the prevalence of mental health disorders in Indonesia from 2013 to 2023, and projects the future burden through 2045. Using panel data from 34 provinces across three time points, the analysis employs a random effects model to capture interregional variation. The findings reveal that annual average temperature is positively and significantly correlated with the prevalence of mental health disorders. Specifically, a 1-degree-Celsius increase in temperature is associated with a 0.5–0.6 percent rise in the proportion of the population experiencing mental health issues. Among socioeconomic factors, unemployment shows a significant positive association, while income inequality, poverty, and unmet need for mental health services are statistically insignificant. The study further constructs long-term projections by integrating regression results with climate and demographic trends. These results highlight the urgency of incorporating mental health dimensions into climate adaptation policies, especially in tropical middle-income countries. A spatial-temporal evidence-based approach is essential for developing early warning systems and responsive policy interventions to address climate-related mental health risks.